Fresnel diffraction from 1D and 2D phase steps in reflection and transmission modes - Amiri, M.; Tavassoly, M.T. (Optics communications, 2007)
When a part of an optical wave-front experiences a sharp change in its phase, Fresnel diffraction becomes appreciable. Sharp change in phase occurs as a wave-front reflects from a step or passes through a transparent medium with abrupt change in thickness or refractive index. Comprehensive study of the subject is useful and significant in many areas, including: coherent and partially coherent imaging, scanning microscopy, optical data storage, and optical metrology. In this report, by applying Fresnel–Kirchhoff integral, we formulate the intensity distribution and its dependence on the step height of the light diffracted from phase steps of 1 and 2 dimensions in reflection and transmission modes. Exploiting Cornu spiral we provide alternative formulation and more tangible interpretation of the results. Also, we study the dependence of the central fringe visibility and its displacement on step height and explore the application potentials of the effect in optical metrology by introducing schemes for designing phase steps of variable heights. Finally, we present some experimental works to illustrate the interesting features of the effect.